1994
DOI: 10.1002/syn.890180105
|View full text |Cite
|
Sign up to set email alerts
|

MPTP‐induced oxidative stress and neurotoxicity are age‐dependent: Evidence from measures of reactive oxygen species and striatal dopamine levels

Abstract: 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) causes marked depletion of dopamine (DA) levels and reduction in the activity of tyrosine hydroxylase (TH) in the nigrostriatal DA pathway. In the brain, the enzyme monoamine oxidase B converts MPTP to 1-methyl-4-phenylpyridinium (MPP+) which enters DA terminals via DA uptake sites. Within the DA terminals, MPP+ blocks the mitochondrial complex I and causes ATP depletion. This is thought to be the main cause of MPTP-induced terminal degeneration. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(55 citation statements)
references
References 31 publications
0
54
0
1
Order By: Relevance
“…It is well established that inhibition of the electron transport generates free radicals. Complex I inhibitors such as rotenone and N-methylpyridinium ion generate free radicals in vivo (Ali et al 1994;Smith and Bennett 1997) and in vitro (Adams et al 1993;Wolvetang et al 1994) as does the complex IV inhibitor, azide (Partridge et al 1994;Smith and Bennett 1997). It has also been reported that mitochondrial complexes are inhibited in animals following OP administration (Li et al 2005;Chan et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…It is well established that inhibition of the electron transport generates free radicals. Complex I inhibitors such as rotenone and N-methylpyridinium ion generate free radicals in vivo (Ali et al 1994;Smith and Bennett 1997) and in vitro (Adams et al 1993;Wolvetang et al 1994) as does the complex IV inhibitor, azide (Partridge et al 1994;Smith and Bennett 1997). It has also been reported that mitochondrial complexes are inhibited in animals following OP administration (Li et al 2005;Chan et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Besides these, several groups have also emphasized the importance of impaired mitochondrial complex I activity as the cause of mitochondrial dysfunction in PD models (4,43,44). Another line of direct evidence for the involvement of decreased complex I activity in the pathogenesis of PD comes from studies administering complex I inhibitors such as rotenone and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine to rodents, which showed mitochondrial dysfunction as well as the loss of dopaminergic neurons (45,46). Interestingly, our results also show the concentration-dependent inhibition of complex I activity by externally added purified ␣-synuclein under in vitro conditions.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, oxidative damage within the *Address correspondence to this author at the University of Denver, Department of Biological Sciences, 2199 S. University Blvd., Denver, CO, 80208; Tel: (303)-871-5654; Fax: (303)-871-3471: E-mail: daniel.linseman@du.edu mitochondria may target complex I of the ETC and further increase ROS production, as is observed in PD [8]. Pathophysiologically relevant complex I inhibitors such as rotenone and N-methylpyridinium ion (MPP + ), generate free radicals and induce disease progression characteristic of PD which is modeled in vitro and in vivo for studies of potential therapeutics [9,10]. Methods aimed at bolstering endogenous antioxidant defense mechanisms to enhance scavenging of free radicals generated during disease progression hold therapeutic potential for neurodegenerative diseases such as PD.…”
Section: Oxidative Stress and Neurodegenerative Diseasementioning
confidence: 97%